The indulgences for the cathedral of Lerida: a further example for the study of fifteenth-century indulgences and material bibliography - Rius Bou, Àngels; de los Reyes Gómez2, Fermín (Revista General de Información y Documentación, 2022)
With a few exceptions, few copies of indulgences are extant, such as the indulgences promulgated for the renovation of the cathedral of Lérida, of which the unsold part of several editions still remains. In total, 449 indulgences printed in the workshop of Enrique Botel, between 1490 and 1495, their rarity lies not only in their large number, which exceeds 400 copies, but also in the variety of their editions and compositions. Of the total of 449 indulgences, 436 of these are in the Archivo Capitular de Lérida. This article describes the genesis of this indulgence, its editions and alterations, and analyzes its characteristics. This may help to understand the production of these complex objects and to add some more information to the study of material bibliography.